STUDY INTO THE DRAIN DOWN CHARACTERISTIC OF SMA CONCRETE USING SANDSTONE AS MINERAL FILLER (FUDMA JOURNAL OF SCIENCES, 2020)
One of the component ingredients in SMA mixtures is mineral filler occupying about 8-10% of asphalt pavement materials (by weight of aggregate). Different types of mineral fillers are used in the SMA mixes such as stone dust, ordinary Portland cement (OPC), slag cement, fly Ash, hydrated lime etc. In this study, sandstone was used as mineral filler and various experimental investigations were carried out to determine its usage as mineral filler in SMA mixes in comparison to the conventional (granite) filler. Marshall Stability and flow analysis as well as density and void analysis were carried out on both samples which yielded an Optimum Binder Content of 5.92% and 6.02% for samples with granite and sandstone filler respectively. Other performance tests were conducted, and the Marshall Stability and flow value determined at OBC are 8.07 kN and 4.4 mm respectively for mixes with granite filler, while 7.58 KN and 4.9 mm was recorded for mixes with sandstone filler. Air voids obtained for both mixes was higher than the specified value of 4% at OBC. Draindown characteristics of both mixes were determined to be 0.24% and 3.3% for mixes with granite and sandstone filler respectively. Indirect Tensile Strength Test was conducted on the samples and SMA with granite filler gave higher strength at lower temperature than SMA with sandstone filler. Therefore, sandstone dusts as mineral filler produces SMA with Higher Draindown characteristics which consequently result in the reduction of the tensile strength of SMA
Keywords: Asphalt Pavement, Stone Dust, Marshal Stability, Granite Filler, Tensile Strength